Quadriceps Strength Influences Patient Function More Than Single Leg Forward Hop During Late-Stage ACL Rehabilitation - Meredith Chaput (North American Sports Medicine Institute, 2021)
# Background A comprehensive battery of tests are used to inform return to play decisions following anterior cruciate ligament (ACL) reconstruction. Performance measures contribute to patient function, but it is not clear if achieving symmetrical performance on strength and hop tests is sufficient or if a patient also needs to meet minimum unilateral thresholds.